First report of onychomycosis caused by Phoma glomerata (Didymella glomerata): case report and literature review. Issue 1 (12th January 2023) - Zarei, Fereshteh; Mahmoudi, Shahram; Amanizadeh, Azam; Agha Kuchak Afshari, Setareh
Abstract : Onychomycosis is the fungal infection of nails caused by yeasts, dermatophytes, and nondermatophyte molds. As a divergent set of fungi can cause onychomycosis, reliable and accurate laboratory identification of the etiological agent is crucial for choosing the proper treatment. Herein, we present a rare case of nondermatophytic onychomycosis of the toenail caused by Phoma glomerata in a 27-year-old Iranian female patient. In addition, a review of the literature on human infections caused by Phoma species is provided.